Pengalihan Piutang (Cessie) Berupa Hak Tanggungan yang Dilakukan oleh Kreditor Separatis terhadap Debitor yang Sudah Dinyatakan dalam Keadaan Insolvensi - Togar Sahat Manaek Sijabat Sijabat; Enaz Olyna Sijabat; Antonius Alreza Pahlevi Marulitua Sitohang; Kris Lihardo Aksana Sijabat (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This journal discusses the legal concept of Cessie as a transfer of claims or debts, especially in the context of banking and credit agreements in Indonesia. Although not explicitly mentioned in the Civil Code, Cessie is regulated through a combination of contract law and property law, particularly regarding the transfer of receivables under a name. Cessie is often used in the world of bankruptcy as a mechanism to transfer the right to collect from Separatist Creditors to another party or third party, usually as collateral for credit facilities. Based on Article 613 of the Civil Code, the transfer of collection rights through Cessie must be carried out in the form of an authentic or private deed, and must be notified in writing to the debtor (cessus). In addition, this transfer only applies to existing claims and requires the debtor's acknowledgment and approval. However, regulations related to the transfer of receivables through Cessie are still considered insufficient to protect Curators in the world of bankruptcy because often the transfer of receivables actually hinders the Curator from carrying out his duties.